Funding dynamics in crowdinvesting - Lars Hornuf; Armin Schwienbacher (Universität Trier, Fachbereich IV – Volkswirtschaftslehre, 2015)
We use hand-collected data from four German crowdinvesting portals to analyze what determines individual investment decisions in crowdinvesting. In contrast with the crowdfunding campaigns on Kickstarter where the typical pattern of project support is U-shaped, we find crowdinvesting dynamics to be L-shaped under a first-come, first-serve mechanism and only U-shaped under a sealed-bid second-price auction. The evidence further shows that investors base their decisions on information provided by the entrepreneur in form of updates during the campaign and by the investment behavior and comments of other crowd investors. We also find evidence for herding behavior. As legislators around the world increasingly regulate crowdinvesting activities, knowing how crowd investors behave under no formal information disclosure provides important insights for issuers, portals, and lawmakers.
Keywords: G11; G20; K22; M13; 330; crowdinvesting; startups; securities issuance; IPO investment dynamics; entrepreneurial finance